Out-of-pocket prescription medicine expenditure amongst community-dwelling adults: Findings from the Irish longitudinal study on ageing (TILDA) in 2016 - James Larkin; Ciaran Prendergast; Logan T. Murry; Michelle Flood; Barbara Clyne; Sara Burke; Conor Keegan; Fiona Boland; Tom Fahey; Nav Persaud; Rose Anne Kenny; Frank Moriarty (Exploratory Research in Clinical and Social Pharmacy)
Background: The number of prescription medicines prescribed to older adults is increasing in Ireland and other countries. This is leading to higher out-of-pocket prescription medicine expenditure for older adults, which has several negative consequences including cost-related non-adherence. This study aimed to characterise out-of-pocket prescription medicine payments, and examine their relationship with entitlements, multimorbidity and adherence. Methods: This cross-sectional study used 2016 data from a nationally-representative sample of adults in Ireland aged ≥50 years. Descriptive statistics and regression models were used to describe out-of-pocket prescription medicine payments and assess the association between out-of-pocket prescription medicine payments and the following variables: healthcare entitlements, multimorbidity, and cost-related non-adherence. Results: There were 5,668 eligible participants. Median annual out-of-pocket prescription medicine expenditure was €144 (IQR: €0–€312). A generalised linear model showed that, amongst those with out-of-pocket prescription medicine expenditure, having fewer healthcare entitlements was associated with 4.74 (95%CI: 4.37–5.15) times higher out-of-pocket prescription medicine expenditure. Overall, 1.7% (n = 89) of participants reported cost-related non-adherence in the previous year. A multivariable model examining cost-related non-adherence found a significant association only for those prescribed 4–5 regular medications (compared to 3 medications) (OR: 1.87, 95%CI: 1.02–3.42). Conclusions: Those with entitlements to subsidised prescription medicines had much lower out-of-pocket prescription medicine expenditure. This highlights the benefits of expanding healthcare entitlements and ensuring uptake of entitlements by those with eligibility.